(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In this article, the effect of one-dimensional waves on a non-deformable moving cylinder located in the ground is studied. The environment model is taken as a grunt [1]. The article defines the kinematic parameters of the cylindrical structure and the stresses generated around the cylinder. According to this model, the relationships between stress and deformation obtained based on experience are assumed to be homogeneous during loading and unloading, that is, the environment is nonlinear. The problem is reduced to a Cauchy problem based on suitable initial conditions. The results of the issue will be presented in the next article.